In-Depth Analysis of HA and NS1 Genes in A(H1N1)pdm09 Infected Patients. - Claudia Caglioti; Marina Selleri; Gabriella Rozera; Emanuela Giombini; Paola Zaccaro; Maria Beatrice Valli; Maria Rosaria Capobianchi (PLoS ONE)
In March/April 2009, a new pandemic influenza A virus (A(H1N1)pdm09) emerged and spread rapidly via human-to-human transmission, giving rise to the first pandemic of the 21th century. Influenza virus may be present in the infected host as a mixture of variants, referred to as quasi-species, on which natural and immune-driven selection operates. Since hemagglutinin (HA) and non-structural 1 (NS1) proteins are relevant in respect of adaptive and innate immune responses, the present study was aimed at establishing the intra-host genetic heterogeneity of HA and NS1 genes, applying ultra-deep pyrosequencing (UDPS) to nasopharyngeal swabs (NPS) from patients with confirmed influenza A(H1N1)pdm09 infection. The intra-patient nucleotide diversity of HA was significantly higher than that of NS1 (median (IQR): 37.9 (32.8-42.3) X 10(-4) vs 30.6 (27.4-33.6) X 10(-4) substitutions/site, p = 0.024); no significant correlation for nucleotide diversity of NS1 and HA was observed (r = 0.319, p = 0.29). Furthermore, a strong inverse correlation between nucleotide diversity of NS1 and viral load was observed (r = - 0.74, p = 0.004). For both HA and NS1, the variants appeared scattered along the genes, thus indicating no privileged mutation site. Known polymorphisms, S203T (HA) and I123V (NS1), were observed as dominant variants (>98%) in almost all patients; three HA and two NS1 further variants were observed at frequency >40%; a number of additional variants were detected at frequency <6% (minority variants), of which three HA and four NS1 variants were novel. In few patients multiple variants were observed at HA residues 203 and 222. According to the FLUSURVER tool, some of these variants may affect immune recognition and host range; however, these inferences are based on H5N1, and their extension to A(H1N1)pdm09 requires caution. More studies are necessary to address the significance of the composite nature of influenza virus quasi-species within infected patients.